Relaxin inhibits cardiac fibrosis and endothelial–mesenchymal transition via the Notch pathway - Zhou X; Chen X; Cai JJ; Chen LZ; Gong YS; Wang LX; Gao Z; Zhang HQ; Huang WJ; Zhou H (Dove Medical Press, 2015)
X Zhou,1 X Chen,2 JJ Cai,2 LZ Chen,3 YS Gong,4 LX Wang,5 Z Gao,1 HQ Zhang,1 WJ Huang,1 H Zhou1 1Department of Cardiology, The First Affiliated Hospital of Wenzhou Medical University, 2Wenzhou Medical University, 3Department of Clinical Laboratory, Wenzhou Central Hospital, 4Institute of Hypoxia Medicine, Wenzhou Medical University, 5Department of Respiratory Medicine, Wenzhou Medical University, Wenzhou, People’s Republic of China Background: Relaxin (RLX) can prevent cardiac fibrosis. We aimed to investigate the possible mechanism and signal transduction pathway of RLX inhibiting cardiac fibrosis.Methods: Isoproterenol (5 mg·kg-1·d-1) was used to establish the cardiac fibrosis model in rats, which were administered RLX. The cardiac function, related targets of cardiac fibrosis, and endothelial–mesenchymal transition (EndMT) were measured. Transforming growth factor β (TGF-β) was used to induce EndMT in human umbilical vein endothelial cells, which were pretreated with RLX, 200 ng·mL-1, then with the inhibitor of Notch. Transwell cell migration was used to evaluate cell migration. CD31 and vimentin content was determined by immunofluorescence staining and Western blot analysis. Notch protein level was examined by Western blot analysis.Results: RLX improved cardiac function in rats with cardiac fibrosis; it reduced the content of collagen I and III, increased the microvascular density of the myocardium, and suppressed the EndMT in heart tissue. In vitro, RLX decreased the mobility of human umbilical vein endothelial cells induced by TGF-β, increased the expression of endothelial CD31, and decreased vimentin content. Compared to TGF-β and RLX co-culture alone, TGF-β + RLX + Notch inhibitor increased cell mobility and the EndMT, but decreased the levels of Notch-1, HES-1, and Jagged-1 proteins.Conclusion: RLX may inhibit the cardiac fibrosis via EndMT by Notch-mediated signaling. Keywords: relaxin, endothelial to mesenchymal transition, transforming growth factor β, myocardial fibrosis, Notch